IDENTIFIKASI SENYAWA KIMIA PADA EKSTRAK ETANOL 96% BIJI ALPUKAT (Persea Americana MILL) DENGAN METODE MASERASI - Nia Lisnawati; Senny Listy Kartika Falestin; PRISTIYANTORO Pristiyantoro; Lulu aulia septiani (Jurnal Farmasi IKIFA, 2025)
Avocado seed (Persea americana Mill) is one of the traditional plants that is easy to find and is usually used by the community to treat several health problems, especially for skin care which contains secondary metabolites which are very beneficial for skin health, namely alkaloids, saponins, flavonoids, and tannins. The purpose of this study was that researchers wanted to know the chemical compounds contained in avocado seeds (Persea americana  Mill) using the maceration method. Maceration can be carried out by soaking the whole or coarsely ground simplicia with solvent in a closed vessel, which is carried out at room temperature for at least three days with repeated stirring until all parts of the plant can dissolve in the solvent. This research method is a descriptive qualitative  experimental  research  to  determine  the  results  of  chemical identification of avocado seed extract. Avocado seed extract was obtained by maceration for 3 days with 96% ethanol. The results of chemical identification showed that avocado seed extract contains active alkaloid compounds which are characterized by a brown precipitate with Wagner reagent and orange precipitate with dragendroff reagent, saponins are indicated by the presence of foam, flavonoids change to red color and tannins are indicated by changes to black- green color. The conclusion in this study is that the 96% ethanol extract of avocado seeds contains alkaloids, saponins, flavonoids, and tanins.